Analysis Hilmi Ali Yafie's Opinion on Gender Equality in Islamic Education and Its Relevance to Madurese Society: (Literature Review of the Book The Rahima Story) - Siti Farida; Wasik Wasik (STAI Syaichona Moh. Cholil Bangkalan, 2024)
Gender equality is the equal rights between men and women. Rahima is an organization that fights for this equality through various activities. This study examines the book